FEATURES OF THE USE OF EMODIA IN THE STUDY OF HUMANITARIAN DISCIPLINES AT THE EXAMPLE OF HISTORY - Romanukha, Oleksandr; Udovichenko, Hannah; Zinchenko, Viktoriia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article deals with the potential to use emoji in the studying process. The purpose of the article is a determination of the potential for use of emoji in the educational process as a partial substitute of the traditional text. There were used the following methods to solve the desired goal: the analysis of the scientific works regarding the matters under the inquiry, synthesis of ideas; generalization of the own pedagogical experience; method for description of the interactive forms of teaching during seminars and lessons in secondary school. The author of this article created the algorithm to use emoji in the history classes at school and university. According to the results of poll among pupils and students emoji is more popular in secondary school. During the classes emoji can be used in various ways: partial emoji translation of the text; emoji testing; quest; using emoji in literary Internet projects. Using emoji has methodical, psychological and technical advantages such as the decrease of the volume of the educational material; the increase of the emotional interest of pupils and students; the development of the logical and associative thinking; conducting classes by dint of smartphones and messengers; distance learning. Using emoji in the studying process engages not only innovation technologies, but also higher nervous system of person, the language of symbolic logic.